EDUCATION PROCESSES AND ELECTRON EDUCATION MANAGE SYSTEM ANALYSIS TO DO - Abdugaffarov Shokhsultan Mavlonbek son; Sultanova Dildora Ilkhomjon daughter (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Abstract : Education processes manage system electron of education variability and competitiveness increased These systems students knowledge to get provide information explanation and appropriation , relative actions perform and to practice of installation mind and efficient methods present is enough This is it in the article education in the process electron of education possibilities and his benefits about data given .